2011
DOI: 10.1021/jp207068m
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interactions of Sodium Salts with Alanine Dipeptide and Tetrapeptide in Water: Insights from Molecular Dynamics

Abstract: We examine computationally the dipeptide and tetrapeptide of alanine in pure water and solutions of sodium chloride (NaCl) and iodide (NaI), with salt concentrations up to 3 M. Enhanced sampling of the configuration space is achieved by the replica exchange method. In agreement with other works, we observe preferential sodium interactions with the peptide carbonyl groups, which are enhanced in the NaI solutions due to the increased affinity of the less hydrophilic iodide anion for the peptide methyl side-chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 85 publications
6
34
0
Order By: Relevance
“…At very high concentrations, the formation of a contact ion pair contributes significantly, and the peak height will decrease. The similar nature of the interaction of cation with the carbonyl oxygen of NMA and anion-amide hydrogen were also found in previous studies of Ioannou et al [70], and the variations are more prominent at concentrated NaI solution comparable to NaCl solution in their study. The ion-water radial distribution functions are largely insensitive to salt concentration as shown in Figures 2(b) and 2(d) and 3(b) and 3(d) but higher peak height of these radial distribution functions indicates the stronger solvation shell of these ions at higher salt concentration.…”
Section: Translational Diffusion and Structure Of The Solvation Shellsupporting
confidence: 89%
See 1 more Smart Citation
“…At very high concentrations, the formation of a contact ion pair contributes significantly, and the peak height will decrease. The similar nature of the interaction of cation with the carbonyl oxygen of NMA and anion-amide hydrogen were also found in previous studies of Ioannou et al [70], and the variations are more prominent at concentrated NaI solution comparable to NaCl solution in their study. The ion-water radial distribution functions are largely insensitive to salt concentration as shown in Figures 2(b) and 2(d) and 3(b) and 3(d) but higher peak height of these radial distribution functions indicates the stronger solvation shell of these ions at higher salt concentration.…”
Section: Translational Diffusion and Structure Of The Solvation Shellsupporting
confidence: 89%
“…Qualitatively, no appreciable difference is observed with non-polarisable force field. Ioannou et al [70] studied computationally the dipeptide and tetrapeptide of alanine in pure water and solutions of sodium chloride (NaCl) and sodium iodide (NaI). It was found that the preferential sodium interactions with the peptide carbonyl groups are enhanced in the NaI solutions due to the increased affinity of the less hydrophilic iodide anion for the peptide methyl side-chains and terminal blocking groups.…”
Section: Introductionmentioning
confidence: 99%
“…AAA, the classical model system of unblocked tripeptides, essentially agrees in suggesting a large pPII content of its conformational distribution. 50, 73 On the contrary, the body of work on blocked dipeptides, particularly AdP, is voluminous, 29, 30, 32, 36, 37, 41-43 starting with the computational work of Ramachandran, Flory, and their coworkers who introduced this peptide as a model system for exhibiting random coil behavior. 18, 19 This view changed only when Han et al reported the results of DFT calculations on AdP in explicit water which clearly revealed a preference for pPII.…”
Section: Resultsmentioning
confidence: 99%
“…8, 13, 14, 18, 19, 28-40 Nearly fifty years after Ramachandran, Flory and co-workers used this peptide 18, 19 as a kind of canonical model system for describing the Ramachandran plot of residues in the unfolded state, numerous MD studies still use this peptide to explore the underlying physics of the pPII preference of alanine. 29, 30, 32, 36-38, 41, 42 Several experimental studies (IR, Raman, NMR) on this peptide have been carried out as well. 13, 15, 33-35, 43 Avbelj and coworkers reported propensity scales for all 19 non-proline residues in blocked dipeptides based on an analysis of the amide III region of their Raman and IR spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation